Use of locust bean gum in flotation separation of chalcopyrite and talc. (15th June 2018) - Feng, Bo; Peng, Jinxiu; Zhang, Wenpu; Ning, Xianghan; Guo, Yutao; Zhang, Wencai
Highlights: Separation of chalcopyrite from talc is difficulty. Locust bean gum has selective depression effect on talc. Locust bean gum adsorbed more on talc surface. Adsorption of locust bean gum on talc is through physical interactions. Abstract: In the flotation separation of chalcopyrite and talc, depressants are usually added to selectively prevent talc from floating. Commonly used depressants lack selectivity, resulting in the depression of both talc and sulfide minerals. To solve this problem, the role of locust bean gum in the flotation separation of chalcopyrite and talc was studied and its mechanism of talc depression discussed. Single mineral flotation test results showed that both chalcopyrite and talc were floatable in the tested pH range of 3–11 and that locust bean gum depressed the flotation of both minerals; however, locust bean gum showed a strong depressing effect on talc in the pH range of 5–9 at a dosage of 2000 g/t. The results of flotation tests performed on mixed minerals indicated that the use of locust bean gum as a depressant can achieve flotation separation of chalcopyrite from talc. A concentrate of 30.1% Cu was achieved at 88.1% recovery from a feed material containing 15.2% Cu. This was attributed to greater adsorption of locust bean gum on the surface of talc compared with that on the chalcopyrite. Zeta potential and X-ray photoelectron spectroscopy measurements showed that the locust bean gum adsorbed on talc mainly through physical interactions; hydrophobic interactions were considered the main driving force and hydrogen bonds also played a role.